Subjective well-being, achievement motivation and entrepreneurial intentions among higher education students - Yuniasanti, Reny; Zahrah, Alimatus; Fitriana, Nina; Budiani, Kondang; Hutagalung, Fonny Dameaty; Zakaria, Abdul Razak (Jurnal Psikologi, 2024)
Background: Nowadays, higher education is increasingly challenged to improve its quality to meet global needs. One of the most concerning indicators of higher education success is the quality of the graduates. To nurture the excellent traits of the alumni, higher education institutions should facilitate the learning process that drives the students to be active in both academic and non-academic areas. Entrepreneurship characters become one important feature in higher education curricular and non-curricular programs. However, the student's enthusiasm for entrepreneurship is still limited. Thus, it is essential to measure the entrepreneurial intention and the factors such as achievement motivation and subjective well-being. Purpose: This research aims to measure the relationship between achievement motivation and subjective well-being to entrepreneurial intention and the relationship between achievement motivation and subjective well-being among higher education students in Indonesia.Method: The respondents of this research are 316 higher education students from many different areas in Indonesia. The data were collected using an online survey with purposive sampling technique. SEM-PLS is employed as the data analysis method in this research.Findings: The result of this study showed that there is a positive relationship between achievement motivation and entrepreneurial intention. Besides, this research also revealed a positive relationship between subjective wellbeing and entrepreneurial intention, and there is a relationship between achievement motivation and subjective well-being.Implication: This information gives insight into intervention for building and enhancing entrepreneurial intention among students to build their achievement and subjective well-being.